Analysis of Problem Solving Ability Polya Stages of Open University Students in Mathematics Courses - Muhassanah, Nur'aini; Winarni, Ambar (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This type of research is qualitative research using a descriptive approach. The purpose of this research is to describe the problem-solving skills of Polya stages in Mathematics courses. The subjects of this study were 15 semester 3 students of the Open University Elementary School Teacher Education Study Program divided into three categories of problem solving abilities, namely 6 students (40%) in the high category, 6 students (40%) in the medium category, and 3 students (20 %) low category. Data related to problem-solving abilities according to Polya's stages were obtained from diagnostic tests and interviews. Subjects were taken by purposive sampling technique and data validation using the triangulation method. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of this study were that most students who were in the high and medium categories were able to write down what was known and asked about the questions correctly, presenting the sequence of completion steps using the right steps or procedures and get the correct results, and write conclusions without writing checks. Meanwhile, a small number of students who were in the low category incompletely wrote down what was known and asked about the questions, the sequence of solutions presented was inaccurate, wrote down the procedures or steps but were incorrect, and wrote conclusions but the answers given were incorrect.